Service quality and its effect on customer satisfaction and loyalty: a study of banks in Chandigarh - Khurana, Arpit (Journal of Social Review and Development, 2025)
The study aimed to examine the factors influencing customer satisfaction in the banking sector of Chandigarh and to analyse the relationship among service quality, customer satisfaction, and customer loyalty. The research adopted a quantitative design and employed the survey method for data collection. Data were gathered from 172 respondents across four different areas using a pre-tested structured questionnaire. The results indicate a significant relationship between various service quality attributes and customer satisfaction. Furthermore, the study found a positive relationship between customer satisfaction and customer loyalty. The findings suggest that higher service quality leads to greater customer satisfaction, which in turn enhances customer loyalty. In an increasingly competitive banking environment, delivering superior service quality can provide banks with a sustainable competitive advantage.